PENDIDIKAN KARAKTER MELALUI CERITA RAKYAT TOBATI, KOTA JAYAPURA - Esther Rita Embram (Kibas Cenderawasih : Jurnal Ilmiah Kebahasaan dan Kesastraan, 2019)
Some of the media in Jayapura city have informed, that crime rates in this city are increasing, largely due to the one of the member of society who consume a high alcohol drink. Theft, rape, beatings, domestic violence, as has been the common thing when staying in this town. Although it must be admitted that was the deviant behavior, has in the various places. The government of Jayapura city are continues to minimize the occurrence of crime in the Jayapura city. It is necessary to have enlightment for people in Jayapura by using existed culture condition in the society. One of them is by using folktale in the indigenous people Jayapura city, as in the story of  Tobati village “Yaci, si Misterius Pembawa Damai”. Disclosure of education values in Port Numbay folklore would contribute to the development of character through the literature character education. This paper is qualitative with an informal presentation methods such as verbal descriptions are systematically arranged.